Mengartikan Persuasi dalam Media Sosial: Studi pada Kampanye Influencer Berdasarkan Prinsip Pathos Aristoteles - Anandati, Fatimah; Sitorus, Phil Fitzerald Kennedy (CV. ITTC INDONESIA, 2024)
Aristotle described persuasion as the process of changing another person's views or behavior using logic, emotion, and ethos (the speaker's character or credibility). This is proven by influencers who carry out campaigns as a step to get optimal results and impressions from the audience. This article aims to describe the meaning of persuasion in social media by taking a study of influencer campaigns based on the principles of Aristotle's Pathos. The research method used is Systematic Literature Review (SLR) with PRISMA guidelines, where the guidelines are a systematic and transparent approach to identifying, evaluating and synthesizing research relevant to a particular topic. The research results show that the implications and relevance of the findings regarding the use of Aristotle's Pathos principle in the context of social media marketing and communication are very broad and significant. Campaigns that utilize emotions effectively tend to attract more attention and engage audiences. Advertisers or influencers can use evocative stories, compelling visuals and appropriate music to create deep emotional engagement. The use of emotions can build stronger bonds between consumers and brands